2006
DOI: 10.1002/hlca.200690022
|View full text |Cite
|
Sign up to set email alerts
|

Novel Steroidal Glycosides from two Indian Caralluma species, C. stalagmifera and C. indica

Abstract: New steroidal glycosides, stalagmosides I -V (1 -5) and indicosides I and II (7 and 8), together with the known compounds carumbelloside III, lasianthoside A, and lasianthoside B, were isolated from whole plants of Caralluma stalagmifera and Caralluma indica, respectively. Their structures were elucidated by extensive NMR spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…It exhibited a UV absorption at 229 nm, and its specific rotation [a] 13 C-NMR data of the aglycone were in agreement with those of stalagmoside II isolated from C. stalagmifera [8]. Therefore, the structure of the aglycone of 1 was determined as (5a) -5,6-dihydrosarcostin 12-acetate 20-benzoate (= (3b,5a,12b,14b,17a,20S)-12-acetoxy-3,8,14,17-tetrahydroxypregnan-20-yl benzoate H-COSY spectra suggested that 1 comprised two 2,6-dideoxy sugars.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…It exhibited a UV absorption at 229 nm, and its specific rotation [a] 13 C-NMR data of the aglycone were in agreement with those of stalagmoside II isolated from C. stalagmifera [8]. Therefore, the structure of the aglycone of 1 was determined as (5a) -5,6-dihydrosarcostin 12-acetate 20-benzoate (= (3b,5a,12b,14b,17a,20S)-12-acetoxy-3,8,14,17-tetrahydroxypregnan-20-yl benzoate H-COSY spectra suggested that 1 comprised two 2,6-dideoxy sugars.…”
mentioning
confidence: 56%
“…The replacement of an AcO group at C(12) by a BzO group was inferred from the 1 H-NMR spectrum (Table 3) The NMR spectroscopic data of the aglycone of 3 were basically identical to those of stalagmoside IV [8], including the deshielding effect observed between the BzO groups. Thus, the structure of 3 was elucidated as (3b,5a,12b,14b,17a,20S)-12,20-bis-(benzoyloxy) -8,14,17-trihydroxypregnan-3-…”
mentioning
confidence: 99%
“…Complete assignment of NMR resonances and comparison with literature data [7] indicated that 1 was (5a,17S)-12-O-benzoyl-3b,8b,12b,14b-tetrahydroxypregnan-20-one ( Table 1). The same skeleton has been found as aglycone in some of the steroidal glycosides isolated from Caralluma species [8].…”
Section: For [M à H]mentioning
confidence: 96%
“…Two known compounds, carumbelloside III and dihydrorusselioside B [13,24] were also isolated from C. pauciflora and β-sitosterol, lupeol, and a known pregnane glycoside were isolated from C. adscendens var. gracilis.…”
Section: Author's Personal Copymentioning
confidence: 99%